Collegiate athletic trainers' experiences with external pressures faced during decision making - Pike Lacy, A. M.; Mazerolle Singe, S.; Bowman, T. G. (Journal of Athletic Training, 2020)
Context: Conflict is prevalent between sports medicine professionals and coaching staffs regarding return-to-play decisions for athletes after injury in the National Collegiate Athletic Association (NCAA) Division I setting. The firsthand experiences of athletic trainers (ATs) regarding such conflict have not been fully investigated. Objective: To better understand the outside pressures ATs face when making medical decisions regarding patient care and return to play after injury in the NCAA Division I Football Bowl Subdivision (FBS) setting. Design: Qualitative study. Setting: Semistructured one-on-one telephone interviews. Patients or Other Participants: Nine ATs (4 men, 5 women; age = 31 ± 8 years [range = 24-48 years]; years certified = 9 ± 8). Data Collection and Analysis: Interviews were audio recorded and later transcribed. Thematic analysis was completed phenomenologically. Researcher triangulation, peer review, and member checks were used to establish trustworthiness. Results: Two major themes emerged from the qualitative analysis: (1) pressure is an expected component of the Division I FBS AT role, and (2) strategies can be implemented to mitigate the negative effects of pressure. Three subthemes supported the second major theme: (1) ensuring ongoing and frequent communication with stakeholders about an injured athlete's status and anticipated timeline for return to play, (2) providing a rationale to coaches or administrations to foster an understanding of why specific medical decisions are being made, and (3) establishing positive relationships with coaches, athletes, and administrations. Conclusions: External pressure regarding medical decisions was an anticipated occurrence for our sample. Such pressure was described as a natural part of the position, not negative but rather a product of the culture and environment of the Division I FBS setting. Athletic trainers who frequently face pressure from coaches and administration should use the aforementioned strategies to improve the workplace dynamic and foster an environment that focuses on patient-centered care. clinician-coach conflict, conflict of interest, organizational culture, role conflict